DOES GENDER AFFECT ATTITUDES IN INCLUSIVE SCHOOLS? EVIDENCE FROM INDONESIAN PRIMARY EDUCATION STUDENTS - Kuswanto, Kuswanto; Fajanela, Jennifer V. Velasquez (International Journal of Education, 2025)
Gender roles influence how inclusive schools are viewed through differences in attitudes, experiences, and social norms attached to gender identity. The aim of this study was to determine the effect of gender on students' attitudes toward inclusive elementary and junior high school, and the difference in average attitudes between males and females. This research was completed with a quantitative approach using descriptive analysis, and an independent-sample t-test. The sample in this study consisted of 431 students consisting of 195 elementary school students and 236 first Junior high school students in Padang city. The results of this study were no influence of gender on students' attitudes towards inclusive and special education, which indicates that both elementary and junior high school students already have a good attitude category. Research conducted by researchers is useful to provide input and information for government and school, and specifically for teachers that students' attitudes towards students with special needs in the view of students have been good and equitable between males and females. That is, tolerance education has been successful. Novelty of research that attitude was not influenced by gender.